(untitled) (The International Journal of Educational Sciences and Arts, 2026)
The study aims to identify the effect of using experiential learning in teaching mathematics on developing procedural fluency among first-grade intermediate female students in Makkah Al-Mukarramah. To achieve this aim, the researcher adopts the experimental method based on a quasi-experimental design. The research instrument, represented by a procedural fluency test, is prepared, and its validity and reliability are verified. The instrument is administered as a pre-test to the two research groups to ensure their equivalence. The study sample is selected purposively and consists of (44) female students, who are divided into an experimental group and a control group. After confirming the equivalence of the two groups, the experimental group is taught using experiential learning, while the control group is taught using the traditional method. The research instrument is then administered to both groups as a post-test. Statistical analyses are conducted to test the validity of the research hypotheses. The results reveal statistically significant differences at the specified level of significance ( ) between the mean scores of the two groups in the post-application of the procedural fluency test, in favor of the experimental group. In light of these results, the study reaches a number of recommendations, most notably applying experiential learning in teaching mathematics across different educational stages and providing training on how to design mathematics lessons based on experiential learning.